Fiqh Madzhab Indonesia (Konsep dan Aplikasi Pemikiran Hasbi As-Siddiqi untuk Konteks Islam Rahmat li-Indonesia) - Suhirman, Gatot (Al-Mawarid Jurnal Hukum Islam, 2010)
The following article investigates historically Fiqh Indonesia raised by Hasbi in 1940, when Indonesia is not independent yet and still to the nationalists against the Dutch colonialists. This can be seen from Indonesia, which is in the term Fiqh Indonesia itself, not the Fiqh of Aceh where Hasbi was born. Of course, should not be forgotten that the word in the term Fiqh Fiqh Indonesia Hasbi also reflects the spirit as a reformer who expressly states that a school will grow faster if adopted by a government. In the context of this kind emphasize the importance of cooperation Hasbi Indonesian Muslims by their government. Hasbi has suggested certainly is not difficult anymore to be developed and accepted by Indonesian Muslims today, considering they are more mature in the national state. Fiqh Indonesia was initiated by Hasbi is the embryo development of understanding of Islam Indonesia in later periods until now.